2014
DOI: 10.1007/s10585-014-9692-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of p75 neurotrophin receptor under hypoxic conditions induces migration and invasion of C6 glioma cells

Abstract: p75 neurotrophin receptor (p75NTR) has been reported to play important roles in various cancer types. However, the exact mechanism of tumorigenesis involving p75NTR is unknown. In this study, we investigated the relationship between the expression of p75NTR in malignant glioma and the impact on tumor cell migration and invasion. p75NTR and hypoxia-inducible factor-1α (HIF-1α) expression was down-regulated by short-hairpin RNA and up-regulated with expression vectors. By immunohistochemical staining and Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Moreover, our finding that the abundance of Fusobacterium is depleted in tumors with LoF mutations in the PDGFR-beta pathway may be explained by the dependence of several pathogenic strains of bacteria for functionally intact PDGFR signaling for adherence to intestinal epithelium [69] . In addition, p75(NTR) signaling has been shown to operate as a tumor suppressor by mediating apoptosis in response to hypoxic conditions and reactive oxygen species [70][71][72][73] . Alterations in this pathway have also been shown to be useful as a biomarker for esophageal cancer [74,75] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our finding that the abundance of Fusobacterium is depleted in tumors with LoF mutations in the PDGFR-beta pathway may be explained by the dependence of several pathogenic strains of bacteria for functionally intact PDGFR signaling for adherence to intestinal epithelium [69] . In addition, p75(NTR) signaling has been shown to operate as a tumor suppressor by mediating apoptosis in response to hypoxic conditions and reactive oxygen species [70][71][72][73] . Alterations in this pathway have also been shown to be useful as a biomarker for esophageal cancer [74,75] .…”
Section: Discussionmentioning
confidence: 99%
“…In normal cells, MMP-9 shows low expression, but high expression in glioma cells. 30,31) TMZ has showed effects on reducing the level of MMP-9. 29) Our work also showed that drug combination group can inhibit the migration of glioma cells by down-regulating the expression of MMP-2 and MMP-9 compared with single drug groups.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other HIF1-regulated pathways may be sensitive to loss of Rb and contribute to this phenotype. Activation of focal adhesion kinase and phosphorylation of paxillin correlate with hypoxia-inducible migration of C6 glioma cells 49 . Up-regulation of vimentin intermediary filaments has been implicated in epithelial-to-mesenchymal transition and increased migratory capacity in lung cancer cells in an AKT-dependent fashion 50 .…”
Section: Discussionmentioning
confidence: 99%